Novel Approach for Robust Control of Axial Piston Pump - Tsonyo Slavov; Alexander Mitov; Jordan Kralev (Mathematics)
The article is devoted to designing novel multivariable robust μ-control of an open-circuit axial piston pump. In contrast with classical solutions of displacement volume control, in our case, the hydro-mechanical controller (by pressure, flow rate, or power) is replaced by an electro-hydraulic proportional valve which receives a control signal from an industrial microcontroller. The valve is used as the actuator of the pump swash plate. The pump swash plate swivel angle determines the displacement volume and the flow rate of the pump. The μ-controller design is performed on the basis of a one-input, two-output model with multiplicative output uncertainty. This model is estimated and validated from experimental data at various loads by multivariable identification. The designed control system achieves robust stability and robust performance for the wide working mode of an axial piston pump. To conduct this experimental study, the authors have developed a laboratory test bench, enabling a real-time function of the control system via USB/CAN communication. The designed controller is implemented in a rapid prototyping system, and real-time experiments are performed. They show the advantages of μ-control and confirm the possibility of its implementation in the case of the real-time control of an axial piston pump.